Attached to dating apps: Attachment orientations and preferences for dating apps. (January 2019) - Chin, Kristi; Edelstein, Robin S.; Vernon, Philip A.
Our study examines attachment-related differences in the use of dating applications (dating apps). We collected online survey data regarding people's attachment orientation and dating app preferences. People with a more anxious attachment orientation were more likely to report using dating apps than people lower in anxious attachment; people with a more avoidant attachment orientation were less likely to report using dating apps than people lower in avoidant attachment. Participants who used dating apps cited Tinder, OkCupid, and Plenty of Fish as those most commonly used. The most common reason people reported for using apps was to meet others, and the most common reason people reported for not using apps was difficulty trusting people online. Our findings suggest that individual differences in attachment may be relevant for understanding online behavior, and that dating apps might be a fruitful avenue for future research on attachment-related differences.